Answer:points
Step-by-step explanation:
(2x + 1)(x + 4)
(2x + 4)(x + 1)
(2x + 2)(x + 4)
Answer:
(2x + 4) ( x +1 ) are factors .
Step-by-step explanation:
Given : 2x² + 9x + 4.
To find : Factor.
Solution : We have given that 2x² + 9x + 4.
On factoring 2x² + 8x + 1x + 4.
Taking common 2x from first two terms and 1 from last two terms .
2x ( x +4 ) +1 (x +4 ).
On grouping
(2x + 4) ( x +1 ).
Therefore , (2x + 4) ( x +1 ) are factors .
The factored form of the polynomial 2x² + 9x + 4 is (2x + 1)(x + 4).
Hence the correct answer is 3rd.
Given is a polynomial 2x² + 9x + 4, we need to factorize it.
To factorize the polynomial 2x² + 9x + 4, we can use the factoring method.
Step 1: Multiply the coefficient of the quadratic term (2) with the constant term (4). In this case, 2 × 4 = 8.
Step 2: Find two numbers that multiply to give 8 and add up to the coefficient of the linear term (9).
In this case, the numbers are 1 and 8 because 1 × 8 = 8 and 1 + 8 = 9.
Step 3: Rewrite the middle term (9x) using the two numbers found in step 2. This will split the middle term into two parts.
2x² + 1x + 8x + 4
Step 4: Group the terms in pairs and factor out the greatest common factor from each pair.
(2x² + 1x) + (8x + 4)
Step 5: Factor out the greatest common factor from each pair.
x(2x + 1) + 4(2x + 1)
Step 6: Notice that we now have a common binomial factor, (2x + 1). Factor out this common binomial.
(2x + 1)(x + 4)
Therefore, the factored form of the polynomial 2x² + 9x + 4 is (2x + 1)(x + 4).
Hence the correct answer is 3rd.
Learn more about Factorization click;
#SPJ6
B. √ 15
C. 30
D. √ 30
Answer:
The answer is the option D
Step-by-step explanation:
we know that
In a right triangle
Applying the Pythagoras Theorem
where
c is the hypotenuse
a and b are the legs
In this problem we have
substitute and solve for b
Please give an explanation to the answer
Answer:
x = 12
Step-by-step explanation:
This equation is very easy to solve.
3x - 13 = 23 Add 13 to both sides of the equation.
3x = 36 Divide by 3 on both sides of the equation.
x = 12
Then, check your answer by substituting the solved value.
3(12) - 13 = 23
36 - 13 = 23
23 = 23
Therefore, x = 12 is the solution to the equation.
Answer:
x = 12
Step-by-step explanation:
3x - 13 = 23
Bring non-variable numbers to other side:
3x = 36
Divide both sides by 3:
x = 12
Vanessa needs at least a 46 on the 4th quiz.
Average is defined as the ratio of the sum of the number of the data sets to the total number of the data. The average actually determines the middle value of the data.
Given that Vanessa has scored 45, 32, and 37 on her three math quizzes. She will take one more quiz and she wants a quiz average of at least 40. The minimum score will be calculated as below:-
First, find the average of the three.
45 + 32 + 37 = 114
114÷3 = 38
4 total quizzes, for a 40 average on 4 quizzes, she needs
40 x 4 = 160 total points
For 3 quizzes she has,
45 +32 +37 = 114 points
For the fourth quiz,
160-114 = 46
Therefore, Vanessa needs at least a 46 on the 4th quiz.
To know more about an average follow
#SPJ2
45 + 32 + 37 = 114
114÷3 = 38
4 total quizzes,
for a 40 average on 4 quizzes she needs 40*4 = 160 total points
for 3 quizzes she has 45 +32 +37 = 114 points
160-114 = 46, she needs at least a 46 on the 4th quiz